PATHOMORPHOLOGICAL ASPECTS OF MODERN WAYS OF SURGICAL TREATMENT IN COMBUSTIOLOGY - S. V. Bogdanov; E. A. Terman; Y. A. Bogdanov (Медицинский вестник Юга России, 2016)
Purpose: to study the pathological aspects of the wound bed in combustiology depending on the surgical treatment methods. Materials and Methods: the histomorphological drugs early after early necrectomy under tow non-perforated grafts at 3, 5 and 7 days after surgery; studied the wound fibrous layer to the plastics granulation by full-thickness transplant. Results: the study examined the dynamics of pathological soft tissue changes in the process of engraftment in the upper and lower extremities, including the use of primary techniques for plastic harness. Studied and described pathological changes in the edges and bottom of the burn wound granulation face to plasticity free skin graft. Summary: histomorphological study engraftment autografts after early treatment, and study of the fibrous layer of granulation is relevant in combustiology, as it allows to predict the quality of engraftment, depending on the localization of the burn wound, healing techniques used, as well as the quality of debridement in the transplant skin graft.